2016
DOI: 10.3171/2016.8.focus16280
|View full text |Cite
|
Sign up to set email alerts
|

Maternal environmental risk factors for congenital hydrocephalus: a systematic review

Abstract: OBJECTIVE Congenital hydrocephalus (CH) is one of the most frequent CNS congenital malformations, representing an entity with serious pathological consequences. Although several studies have previously assessed child-related risk factors associated with CH development, there is a gap of knowledge on maternal environmental risk factors related to CH. The authors have systematically assessed extrinsic factors in the maternal environment that potentially confer an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
20
1
Order By: Relevance
“…Several covariates were evaluated as potential confounders or effect modifiers based on previously described associations with the birth defects of interest or PAHs in the literature (Anderson et al, 2005;Bhatti et al, 2003;Canfield, Langlois, Nguyen, & Scheuerle, 2009;Croen et al, 2000;Forrester & Merz, 2006;Hackshaw et al, 2011;Johnson & Rasmussen, 2010;Kalyvas et al, 2016;Kancherla et al, 2014;Mastroiacovo et al, 1995;Miller et al, 2010;Prakalapakorn, Rasmussen, Lambert, & Honein, 2010;Reeder et al, 2015;Shaw, Carmichael, Kaidarova, & Harris, 2003Stothard, Tennant, Bell, & Rankin, 2009;Zhang, Zhang, Yu, & Shen, 2009): maternal age at delivery; maternal race/ethnicity; maternal prepregnancy body mass index (BMI); maternal diabetes; maternal smoking; maternal alcohol consumption; maternal exposure to second-hand smoke at home or work; infant sex; gestational age of infant at birth; and infant birthweight. Study center was also considered.…”
Section: Covariatesmentioning
confidence: 99%
“…Several covariates were evaluated as potential confounders or effect modifiers based on previously described associations with the birth defects of interest or PAHs in the literature (Anderson et al, 2005;Bhatti et al, 2003;Canfield, Langlois, Nguyen, & Scheuerle, 2009;Croen et al, 2000;Forrester & Merz, 2006;Hackshaw et al, 2011;Johnson & Rasmussen, 2010;Kalyvas et al, 2016;Kancherla et al, 2014;Mastroiacovo et al, 1995;Miller et al, 2010;Prakalapakorn, Rasmussen, Lambert, & Honein, 2010;Reeder et al, 2015;Shaw, Carmichael, Kaidarova, & Harris, 2003Stothard, Tennant, Bell, & Rankin, 2009;Zhang, Zhang, Yu, & Shen, 2009): maternal age at delivery; maternal race/ethnicity; maternal prepregnancy body mass index (BMI); maternal diabetes; maternal smoking; maternal alcohol consumption; maternal exposure to second-hand smoke at home or work; infant sex; gestational age of infant at birth; and infant birthweight. Study center was also considered.…”
Section: Covariatesmentioning
confidence: 99%
“…The systematic review showed that complete lack of prenatal care is strongly associated with CH specifically and initiating prenatal care after the 8 th month of gestation is also related to the development of CH. 9 The present study highlights the lack of prenatal care in women bearing babies with congenital hydrocephalus. It is apparent from our study that most (94.30%) of these women presented in third trimester when the foetal condition was diagnosed.…”
Section: Discussionmentioning
confidence: 69%
“…1 Hence, findings should be interpreted cautiously and regarded as possible future avenues of research under epidemiological, clinical, and preclinical settings. 9,14,15,16 CONCLUSION First or second pregnancies of young, illiterate women from rural background are more prone to congenital hydrocephalus. Even though a genetic basis has been speculated, most of the causative factors still remain unclear for this disorder which has wide ranging health and financial implications for the affected individuals and their families.…”
Section: Discussionmentioning
confidence: 99%
“…Maternal infections and trauma to the mother during pregnancy have also been highlighted as potential mother-related risk factors. 9 Despite the significant investment in improving maternal healthcare, disparities exist between socio-economic strata and this has an influence on the incidence of hydrocephalus, which explains the high number of cases within the public health sector.…”
Section: Discussionmentioning
confidence: 99%